2011
DOI: 10.1371/journal.pone.0025464
|View full text |Cite
|
Sign up to set email alerts
|

Entry Pathways of Herpes Simplex Virus Type 1 into Human Keratinocytes Are Dynamin- and Cholesterol-Dependent

Abstract: Herpes simplex virus type 1 (HSV-1) can enter cells via endocytic pathways or direct fusion at the plasma membrane depending on the cell line and receptor(s). Most studies into virus entry have used cultured fibroblasts but since keratinocytes represent the primary entry site for HSV-1 infection in its human host, we initiated studies to characterize the entry pathway of HSV-1 into human keratinocytes. Electron microscopy studies visualized free capsids in the cytoplasm and enveloped virus particles in vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 50 publications
11
82
1
2
Order By: Relevance
“…How these alternative pathways correlate with nectin-1 internalization has still to be shown. The dual internalization mode in murine keratinocytes is in line with our results for human keratinocytes, where HSV-1 uptake occurs by direct fusion with the plasma membrane and by endocytic vesicles, in a process which requires dynamin and is dependent on cholesterol (27).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…How these alternative pathways correlate with nectin-1 internalization has still to be shown. The dual internalization mode in murine keratinocytes is in line with our results for human keratinocytes, where HSV-1 uptake occurs by direct fusion with the plasma membrane and by endocytic vesicles, in a process which requires dynamin and is dependent on cholesterol (27).…”
Section: Discussionsupporting
confidence: 89%
“…Murine epidermal whole mounts from wt or nectin-1-deficient mice were fixed with 3.4% formaldehyde as described previously (27) and then stained overnight with mouse anti-ICP0 (monoclonal antibody [MAb] 11060) (28) diluted 1:60, followed by washing with PBS-0.2% Tween 20 for 4 h, overnight incubation with anti-mouse immunoglobulin G (AF488) (Life Technologies) and DAPI (4=,6-diamidino-2-phenylindole), and washing with PBS-0.2% Tween 20 for 4 h, all at room temperature. Murine epidermal cryosections from wt or nectin-1-deficient mice were embedded in Tissue Tek (Sakura) and frozen in liquid nitrogen; 10-m frozen cross sections were then cut using a CM3050 (Leica) cryomicrotome.…”
Section: Rna Preparation and Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…Previously, we have shown that uptake into keratinocytes, the major cell type of the epidermis, depends on the multidomain GTPase, dynamin (37). To further characterize the internalization pathway in primary fibroblasts, we investigated the role of dynamin.…”
Section: Resultsmentioning
confidence: 99%
“…We have also previously shown that cholesterol is required for HSV-1 uptake into human primary keratinocytes, highlighting the role of cholesterol-rich lipid rafts (37). To investigate the role of cholesterol in primary dermal fibroblasts, we treated them with M␤CD, which depletes cholesterol from the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…One other example is herpes simplex virus type 1 (HSV-1). Although previous studies had indicated that the endocytosis of HSV-1 involves macropinocytosis [77], but Clement and Rahn have discovered that, the HSV-1, can take another route; a phagocytosis-like uptake that is facilitated by nectin-1, dynamin, and cholesterol-dependent manner [78,79]. In�uenza virus as mentioned above, enter host cells mainly via clathrin-mediated endocytosis.…”
Section: Unusual Endocytic Pathwaysmentioning
confidence: 99%